Hijacking the Hexosamine Biosynthetic Pathway to Promote EMT-Mediated Neoplastic Phenotypes - Taparra, Kekoa; Tran, Phuoc T.; Zachara, Natasha E. (Frontiers in Oncology, 2016)
The epithelial-mesenchymal transition (EMT) is a highly conserved program necessary for orchestrating distant cell migration during embryonic development. Multiple studies in cancer have demonstrated a critical role for EMT during the initial stages of tumorigenesis and later during tumor invasion. Transcription factors (TFs) such as SNAIL, TWIST, and ZEB are master EMT regulators that are aberrantly overexpressed in many malignancies. Recent evidence correlates EMT-related transcriptomic alterations with metabolic reprogramming in cancer. Metabolic alterations may allow cancer to adapt to environmental stressors, supporting the irregular macromolecular demand of rapid proliferation. One potential metabolic pathway of increasing importance is the hexosamine biosynthesis pathway (HBP). The HBP utilizes glycolytic intermediates to generate the metabolite UDP-GlcNAc. This and other charged nucleotide sugars serve as the basis for biosynthesis of glycoproteins and other glycoconjugates. Recent reports in the field of glycobiology have cultivated great curiosity within the cancer research community. However, specific mechanistic relationships between the HBP and fundamental pathways of cancer, such as EMT, have yet to be elucidated. Altered protein glycosylation downstream of the HBP is well positioned to mediate many cellular changes associated with EMT including cell-cell adhesion, responsiveness to growth factors, immune system evasion, and signal transduction programs. Here we outline some of the basics of the HBP and putative roles the HBP may have in driving EMT-related cancer processes. With novel appreciation of the HBP’s connection to EMT, we hope to illuminate the potential for new therapeutic targets of cancer.